Factors Influencing 5G Adoption in Java: A Theory of Consumption Value and Stimulus-Organism-Response Approach - Kesumahadi, Lisdianto Dwi; Nuruzzaman, Muhammad Taufiq; Sugiantoro, Bambang; Sumarsono , Sumarsono (Universitas Ahmad Dahlan, 2025)
The rapid advancement of information and communication technology has led to a significant transformation in telecommunication networks, particularly with the introduction of 5G technology, which offers high speed, low latency, and extensive device connectivity. However, the adoption of 5G in Indonesia, particularly in Java, remains challenging due to unequal network distribution and disparities in purchasing power between urban and rural areas. This study examines the key factors influencing consumer acceptance of 5G services in Java using the Theory of Consumption Value (TCV) and Stimulus-Organism-Response (SOR) framework. A descriptive quantitative approach was applied, collecting primary data from 200 respondents through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that Safety Affordance and Facilitation Conditions significantly influence consumption value, whereas Visibility Affordance and Guidance Affordance do not. These results highlight the importance of security perceptions and supporting infrastructure in 5G adoption. This study contributes to the theoretical understanding of technology adoption by integrating TCV and SOR in the context of 5G and provides practical recommendations for policymakers and service providers to enhance 5G implementation, particularly by addressing infrastructure gaps in rural areas.